HUBUNGAN USIA MENARKE IBU DAN USIA MENARKE ANAK PADA ANAK KELAS 5 DAN 6 SD NEGERI I, III, IV PUCANGAN KECAMATAN KARTASURA SUKOHARJO - Budi Santoso; Vivi Buari Putri (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractA first menstrual bleeding (is called menarche), as one of the sign of puberty, is veryimportant event in the reproductive life of a woman. Age at menarche is affected by twomajor factors/determinats, genetic and non genetic (environmental), reflects the healthstatus of a population. In recent years, the average age at menarche showed acontinuous trend for earlier, although this trend tends to slow down or stabilize. EarlyAAM may be associated with social and medical problems in later life. This study wasdesigned to determine the relationship of mothers age at menarche and their postmenarchealdaughters at grades 5 and 6 in three Pucangan public elementary schools(SD Negeri I, III, IV Pucangan). Similarity of Elementary School’s location (in thePucangan Village), have a tendency in common areas of residence, socioeconomicstatus, and other non-genetic determinants, so the researchers wanted to know therelationship between menarcheal age of mothers and their daughters.Subject were 31 female students at grades 5 and 6 in SD Negeri, I, III, IV Pucangan,District of Kartasura Sukoharjo. The sampling technique to be used is saturated samplinginwich all of the population to be used as sample.This cross sectional study used Pearson correlation test (with α = 0.05) to analyze dataand obtained p value of 0.402 to p > 0.05 which means that Ho : accepted and Ha :rejected. The result showed that there was no relationship between menarcheal age ofmothers and their daughters at grades 5 and 6 in SD Negeri I, III, IV Pucangan, District ofKartasura Sukoharjo.Keywords : Menarche, Age at Menarche, Genetic Determinants